Thermal modelling of feedwater heaters - Allie, Mohammed Nazier (Department of Mechanical Engineering, 2016)
Manufacturers of feedwater heaters (FWHs) are obliged to disclose a specification sheet to the client that describes their FWH design. However, the client is unable to verify the performance of this FWH design without comparing it to the results that are predicted by a thermal model. An additional limitation is that the manufacturer will only disclose the minimum number of design parameters. The purpose of this study was to develop a thermal model that can predict the performance of a FWH. The model requires the minimum design input data to predict the performance parameters that may be compared to values predicted by the vendor. A FWH in a regenerative water-steam Rankine cycle achieves heat transfer to the feedwater by condensing steam on the shell side. This is called a single zone FWH. The tube plate type FWH is the most common type of FWH referenced in literature but the following variations may exist: • The Eskom fleet consist of both tube plate and header type FWHs. • FWHs may be orientated vertically or horizontally. Internal shrouded regions, that define it as a 2 or 3 zone FWH, may be present in the FWH. The length of the drains cooler (DC) zone may either be identified as long or short. A general model was required to capture all these design variations. Plant visits were arranged with engineers at several power stations to obtain the minimum input data and to confirm that these FWH design variations existed within the Eskom fleet. The model was based on existing tube plate models found in literature. It was then extended to accommodate the FWH variations mentioned above. A further improvement was made by including an additional heat transfer sub-zone that removes excess superheat in the condensing (COND) zone. The vendor does not disclose the correlations used to predict the film heat transfer coefficients (h) in their design. Therefore, the user is granted the option of selecting a correlation from a list of popular correlations, specific to a heat transfer mode. Note that the uncertainty associated with this thermal model is affected by the uncertainty of each correlation selected in the model.